PENGARUH BEBAN KERJA, DISIPLIN, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI RSUD WONOSARI - Heru Kuncorowati; Diana Leli Indratno; Ria Andriani; Lalu Supardin (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the effect of workload, work discipline, and compensation on employee performance. Data collection in this research used a survey with a questionnaire. The sample in this study was 100 respondents and the sampling technique used probability sampling with random sampling techniques. The analytical tool used in this research uses multiple linear regression with SPSS 26 software. The findings in this research show that: First, workload has a significant positive effect on the performance of employees at Wonosari Hospital. Second, work discipline has a significant positive effect on the performance of Wonosari Regional Hospital employees. Third, compensation has a significant positive effect on the performance of Wonosari Hospital employees. Keywords: Workload, Work Discipline, Compensation, and Employee Performance.